2015
DOI: 10.1093/mnrasl/slu206
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on changes in the proton–electron mass ratio using methanol lines

Abstract: We report Karl G. Jansky Very Large Array (VLA) absorption spectroscopy in four methanol (CH 3 OH) lines in the z = 0.88582 gravitational lens towards PKS1830−211. Three of the four lines have very different sensitivity coefficients K µ to changes in the proton-electron mass ratio µ; a comparison between the line redshifts thus allows us to test for temporal evolution in µ. We obtain a stringent statistical constraint on changes in µ by comparing the redshifted 12.179 GHz and 60.531 GHz lines, [∆µ/µ] 1.1 × 10 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 53 publications
5
79
0
Order By: Relevance
“…On the other hand, CH 3 OH, HNCO, HC 3 N, and CH 3 NH 2 were found with blueshifted centroids (∼−5 km s −1 ), such as CH 3 OH here. A similar centroid was found by Kanekar et al (2015) on the line profile of several CH 3 OH lines observed at good signal-to-noise ratio with the Jansky Very Large Array. The time variations of the absorption (Muller & Guélin 2008;Muller et al 2014a) hamper the comparison of line profiles across time, but at a given epoch, the relative offsets of the line velocity centroids between different species are meaningful.…”
Section: Resultssupporting
confidence: 83%
“…On the other hand, CH 3 OH, HNCO, HC 3 N, and CH 3 NH 2 were found with blueshifted centroids (∼−5 km s −1 ), such as CH 3 OH here. A similar centroid was found by Kanekar et al (2015) on the line profile of several CH 3 OH lines observed at good signal-to-noise ratio with the Jansky Very Large Array. The time variations of the absorption (Muller & Guélin 2008;Muller et al 2014a) hamper the comparison of line profiles across time, but at a given epoch, the relative offsets of the line velocity centroids between different species are meaningful.…”
Section: Resultssupporting
confidence: 83%
“…The methanol (Jansen et al 2011;Levshakov, Kozlov & Reimers 2011) and ammonia (Flambaum & Kozlov 2007) molecules are very sensitive to μ variations. Observations of methanol lines in PKS1830−211 at a redshift of 0.88582 by Bagdonaite et al (2013) and Kanekar et al (2015) have restricted μ/μ to ( − 2.9 ± 5.7) × 10 −8 , where the error is the combined statistical and systematic 1σ error. Concerns about common lines of sight have increased the error to ±1.0 × 10 −7 which is the constraint on the variation of μ used in this work.…”
Section: The Proton To Electron Mass Ratio μ Observationsmentioning
confidence: 99%
“…The radio observations, however, are significantly more accurate than the optical H 2 observations. The radio observations of methanol in PKS1830-211 [12] ( ∆µ µ = (−2.9 ± 10) × 10 −8 ) at a redshift of 0.88582 is currently the tightest constraint on a variation of µ. In spite of the relatively low redshift, the look back time is greater than half the age of the universe.…”
Section: µ Constraintsmentioning
confidence: 99%
“…These constraints come from using (13) in (12). The ± in the ∆α α and ∆µ µ terms in Equations (14) and (15) simply reflect that limits on dα α and dµ µ are plus or minus the quoted error.…”
Section: Individual Constraints Onmentioning
confidence: 99%